PERAN EKSKLUSIF ORANG TUA DALAM MEMBENTUK KONSEP DIRI REMAJA KRISTEN - Sostenis Nggebu (SOLA GRATIA: Jurnal Teologi Biblika dan Praktika)
Abstract:  The study of this article is directed at shaping the self-concept of Christian youth. The self-concept is so essential to their existence that its fulfillment requires the active role of their parents. According to God’s will, the formation of youth self-concept is an exclusive call from God for parents to build youth into the likeness of Jesus Christ. The author uses the literature study method to explain adolescents’ healthy self-concepts to deepen the discussion. Through this study, the authors found an essential fact that adolescents’ self-concept is closely related to the coaches of adolescents in a constructive and applicable manner. Parents have the primary responsibility in guiding youth to become accustomed to hearing God’s word and obeying the requirements of Jesus Christ for their lives. In managing a harmonious relationship with God, they learn to discover for themselves the dynamics of life by walking in God’s word and are able to apply God’s truth in their lives. In this aspect, they will grow into the likeness of Jesus Christ and mature in faith as a tangible manifestation of the actualization of a healthy and true self-concept according to the Christian faith. Abstrak: Kajian artikel ini diarahkan pada pembentukan konsep diri para remaja Kristen. Konsep diri begitu penting bagi eksistensi mereka maka pemenuhannya memerlukan peran aktif orang tua mereka. Pembentukan konsep diri remaja yang sesuai dengan kehendak Allah merupakan panggilan yang eksklusif dari Allah bagi  orang tua untuk membina para remaja menjadi milik Yesus Kristus. Untuk mendalami pembahasannya, penulis menggunakan metode studi pustaka dalam menjelaskan konsep diri yang sehat bagi para remaja. Melalui studi tersebut, penulis menemukan fakta penting bahwa dalam konsep diri remaja erat kaitan dengan pembina terhadap para remaja secara konstruktif dan aplikatif. Orang tua memiliki tanggung jawab utama dalam menuntun para remaja agar membiasakan diri dengar-dengaran akan firman Allah dan taat pada tuntutan Yesus Kristus bagi hidup mereka. Dalam menata hubungan yang harmonis dengan Tuhan, mereka belajar menemukan sendiri dinamika hidup dengan berjalan dalam firman Allah dan mampu menerapkan kebenaran Allah itu di dalam hidup mereka. Dalam aspek inila mereka akan bertumbuh menjadi serupa dengan Yesus Kristus dan menjadi dewasa dalam iman sebagai wujud nyata dari aktualisasi dari konsep diri yang sehat dan benar sesuai iman Kristen.